NudC L279P Mutation Destabilizes Filamin A by Inhibiting the Hsp90 Chaperoning Pathway and Suppresses Cell Migration - Liu, Min; Xu, Zhangqi; Zhang, Cheng; Yang, Chunxia; Feng, Jiaxing; Lu, Yiqing; Zhang, Wen; Chen, Wenwen; Xu, Xiaoyang; Sun, Xiaoxia; Yang, Mingyang; Liu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Filamin A, the first discovered non-muscle actin filament cross-linking protein, plays a crucial role in regulating cell migration that participates in diverse cellular and developmental processes. However, the regulatory mechanism of filamin A stability remains unclear. Here, we find that nuclear distribution gene C (NudC), a cochaperone of heat shock protein 90 (Hsp90), is required to stabilize filamin A in mammalian cells. Immunoprecipitation-mass spectrometry and western blotting analyses reveal that NudC interacts with filamin A. Overexpression of human NudC-L279P (an evolutionarily conserved mutation in NudC that impairs its chaperone activity) not only decreases the protein level of filamin A but also results in actin disorganization and the suppression of cell migration. Ectopic expression of filamin A is able to reverse these defects induced by the overexpression of NudC-L279P. Furthermore, Hsp90 forms a complex with filamin A. The inhibition of Hsp90 ATPase activity by either geldanamycin or radicicol decreases the protein stability of filamin A. In addition, ectopic expression of Hsp90 efficiently restores NudC-L279P overexpression-induced protein stability and functional defects of filamin A. Taken together, these data suggest NudC L279P mutation destabilizes filamin A by inhibiting the Hsp90 chaperoning pathway and suppresses cell migration.